New annual estimates of Swedish GDP, 1800–20101. (16th April 2013) - Edvinsson, Rodney
<x xml:space="preserve">Abstract</x> Although the historical national accounts of Sweden are among the most detailed in the world, there is scope for improvement. This study revises previous historical estimates of Swedish GDP. Agricultural output is upgraded for the nineteenth century following recent research by Swedish agrarian historians on the underestimation of official statistics. Estimates of annual fluctuations before 1861 are significantly improved by using new sources on yield ratios of harvests. For manufacturing, home industries are added, in accordance with modern international guidelines (2008 SNA). The study concludes that early nineteenth‐century Sweden was not as poor relative to other West European countries as previously thought.